An Empirical Comparison of the Four Channel Flow Model and Adventure Experience Paradigm - Jones, Christopher D.; Hollenhorst, Steven J.; Perna, Frank (Leisure sciences, 2003)
The objective of this study was to conduct empirical comparisons between two models of optimal experience within an on-site whitewater kayaking setting using a modification of the Experience Sampling Method. Four concerns are examined: (1) differences in explanatory power between the four channel flow model and the Adventure Experience Paradigm, (2) convergent validity among measures used to determine conditions within these models, (3) differences among measures of perceived challenge and risk between test times of Class I-V river difficulty, and (4) differences among measures of perceived skill and competence between test times of Class I-V river difficulty. Questionnaires were administered in the Cheat River Canyon in West Virginia to 52 whitewater kayakers at eight sites of various levels of river difficulty. Data were analyzed at the experience level, rather than between subjects, using 409 experience sampling observations. Hypothesis testing, performed with statistical analyses (stepwise regression, correlations, and repeated measures ANOVA), suggested that the explanatory powers of the four channel flow model and Adventure Experience Paradigm were similar and indicated support for convergent and ecological validity of measures used to determine conditions within each of the two models.